Large-scale Degradation of the Tocantins-Araguaia River Basin - Pelicice, Fernando Mayer; Agostinho, Angelo Antonio; Akama, Alberto; Andrade Filho, José Dilermando; Azevedo-Santos, Valter M. [UNESP]; Barbosa, Marcus Vinicius Moreira; Bini, Luis Mauricio; Brito, Marcelo Fulgêncio Guedes; dos Anjos Candeiro, Carlos Roberto; Caramaschi, Érica Pellegrini; Carvalho, Priscilla; de Carvalho, Rodrigo Assis; et al. (Springer Nature, 2021)
The Tocantins-Araguaia Basin is one of the largest river systems in South America, located entirely within Brazilian territory. In the last decades, capital-concentrating activities such as agribusiness, mining, and hydropower promoted extensive changes in land cover, hydrology, and environmental conditions. These changes are jeopardizing the basin’s biodiversity and ecosystem services. Threats are escalating as poor environmental policies continue to be formulated, such as environmentally unsustainable hydropower plants, large-scale agriculture for commodity production, and aquaculture with non-native fish. If the current model persists, it will deepen the environmental crisis in the basin, compromising broad conservation goals and social development in the long term. Better policies will require thought and planning to minimize growing threats and ensure the basin’s sustainability for future generations.
Keywords: Biodiversity; Conservation; Policy; South America; Sustainability